2010
DOI: 10.3109/14017431.2010.519401
|View full text |Cite
|
Sign up to set email alerts
|

Eight years of pulmonary valve replacement with a suggestion of a promising alternative

Abstract: Although the follow-up for the Perimount valves was short, they are promising and need to be followed long-term. The homograft and the Monocusp remain valuable choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The mortality for pulmonary valve replacement was lower than that reported in a study from Norway, which included 79 patients over the age of 17 receiving a pulmonary valve replacement with overall early mortality of 2.7%. 22 Shinkawa et al analyzed 73 patients undergoing pulmonary valve replacement and reported zero perioperative deaths. 23 Mortality for atrial septal defect repair was zero in our study and has previously been reported to be 0–1.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality for pulmonary valve replacement was lower than that reported in a study from Norway, which included 79 patients over the age of 17 receiving a pulmonary valve replacement with overall early mortality of 2.7%. 22 Shinkawa et al analyzed 73 patients undergoing pulmonary valve replacement and reported zero perioperative deaths. 23 Mortality for atrial septal defect repair was zero in our study and has previously been reported to be 0–1.2%.…”
Section: Discussionmentioning
confidence: 99%
“…[16] It was also reported that the Contegra conduit responded better to catheter interventions, when stenosis developed. Neukamm et al [17] described that necessity for reoperations within the first two years was significantly lower for Contegra grafts than for non-blood group compatible cryopreserved homografts, two of 78 (2.6%) and eight of 20 (40.0%), respectively. However, there are also studies reporting that distal anastomotic stenosis after the Contegra use is more frequent, and that some conduits may lead to pulmonary insufficiency associated with significant conduit dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Structural deterioration of the Contegra graft may be seen in small number of patients (5.1%) 31 . Necessity for reoperations within the first 2 years was significantly lower for Contegra grafts than for non-blood group compatible cryopreserved homografts, 2 of 78 (2.6%) and 8 of 20 (40.0%), respectively 33 . Contegra grafts had reoperations due to insufficiency in only 6%, however, reoperations were mainly due to peripheral pulmonary stenosis at the distal anastomosis and aneurysms 34 .…”
Section: Conduit Failurementioning
confidence: 99%
“…Conduit plasty was necessary in 6 (0.4%), and reintervention to the conduit or to the pulmonary arteries in 83 (4.9%) patients. The conduit reimplantation was due to severe stenosis (excessive gradient) of the distal anastomosis refractory to interventional treatment 9,14,24,33,35 , (pseudo)aneurysm of the proximal anastomosis 19 , progressive right ventricular dysfunction caused by severe conduit regurgitation 18,20,33 , endocarditis 11,35 or graft degeneration 35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation